GPU‐accelerated simulation of a non‐local conservation law. Issue 1 (25th January 2021) - Göttlich, Simone; Müller, Jann; Weissen, Jennifer
Abstract: The model under consideration is a non‐local conservation law in two space dimensions that might be used to model material or pedestrian flow. We accelerate the simulation of the non‐local model using parallelization of the non‐local terms in the programming language Haskell. The implementation allows for the computation of the solution to the conservation law with a finite volume method at reasonable computational cost even for large domains and fine discretizations.